Penentuan Lokasi Jaringan Iconnet Di Kabupaten Aceh Tengah Menggunakan Google Earth Di PT. Oregon Lintas Nusa - Zulfa, Ira; Sentosa, Edi (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Advances in information technology in every aspect of today's needs have made information technology a functionality of social life. The internet has now become an inseparable part of our lives. All aspects of life have started to use internet facilities, not only large companies that want to market their products widely but also government organizations, political parties, institutions, foundations, and even individuals have also used the internet for convenience in providing services and information, as well as for ease of needs and development. business. In Central Aceh District itself, there are several internet network infrastructure service providers, one of which is the vendor PT. Oregon Lintes Nusa is an iconnet internet network service provider. However, because the area allocation is still in the process of expanding, there are still many areas that have not been covered by the Iconnet network itself, which makes it difficult for consumers to know the point of the Iconnet network. Therefore the author is interested in conducting research and finding solutions to these problems, so the title of this internship report is Iconnet Network Point Location Training in Central Aceh District Using Google Earth.